A study on request strategies practiced by Malaysian credit officers. - Wan Abdullah, Wan Narmi Aziana ([s.n], 2012)
Many studies have been done on the non-native speakers’ pragmalinguistic and politeness related interactions by contrasting the data with native speakers’ discourse, for instance in areas of expression of apologies (Cohen & Olshtain, 1981) and requests (Blum-Kulka, 1982). What these studies show is that learning a second language does not only involve the vocabulary, grammar or pronunciation rules, but second language learning also involves the knowledge and ability to use the linguistic competence in an appropriate manner suitable for whichever social context the individual is in. It has been observed that non-native speakers have difficulty expressing politeness appropriately especially if the target language is not their own and therefore the expressions of politeness may differ. Considering the lack of local data in this area, this study aims to provide more information as well as assist language instructors in planning the curriculum for specific areas of English for Specific Purposes (ESP). Currently what occurs for this subject is that it provides language instruction for a wide scope, for instance, English for Business and Economics, English for Science and Technology and so on. However, in this wide scope, ESP does not focus on sub-areas of a particular field which is also important.